CRITICS AND ACTUAL RESULTS OF THE STATE SUPPORT FOR YOUNG FAMILIES DURING THE FIDESZ GOVERNMENT - Roland A. Csizmazia (PEOPLE: International Journal of Social Sciences, 2025)
In response to declining birth rates, Hungary has introduced wide-ranging family support programs under Prime Minister Viktor Orbán’s government. This case study explores how financial incentives—such as the Baby Expecting Loan (Babaváró Hitel), housing subsidies (CSOK), and tax benefits—have influenced family decisions since the 2010s. The research examines whether these policies have led to a lasting rise in fertility, primarily helped certain social groups, or mainly served political goals. It draws on demographic data, government documents, and budget information to assess the real impact of Hungary’s pro-family agenda. The study also looks at the ideological side of these policies, including their emphasis on traditional family values and their role in broader political strategies. The findings offer insight into how state support can shape reproductive choices and may help inform other countries facing similar demographic challenges.